Postmating female control: 20 years of cryptic female choice - Firman, R; Gasparini, C; Manier, M; Pizzari, T (Cell Press, 2017)
Cryptic female choice (CFC) represents postmating intersexual selection arising from female-driven mechanisms at or after mating that bias sperm use and impact male paternity share. Although biologists began to study CFC relatively late, largely spurred by Eberhard's book published 20 years ago, the field has grown rapidly since then. Here, we review empirical progress to show that numerous female processes offer potential for CFC, from mating through to fertilization, although seldom has CFC been clearly demonstrated. We then evaluate functional implications, and argue that, under some conditions, CFC might have repercussions for female fitness, sexual conflict, and intersexual coevolution, with ramifications for related evolutionary phenomena, such as speciation. We conclude by identifying directions for future research in this rapidly growing field.